2021
DOI: 10.5210/fm.v26i2.10317
|View full text |Cite
|
Sign up to set email alerts
|

Archiving affect and activism: Hashtag feminism and structures of feeling in Women's March tweets

Abstract: On 21 January 2017, over three million women participated in the Women’s March throughout the U.S., one day after President Donald Trump’s inauguration. This article investigates the digital component of this historic protest as a powerful moment of hashtag feminism, one that exemplifies the vital role of affect in contributing to social change. Through qualitative analysis of 2,600 #WhyIMarch tweets from the day of the March, we identify the rhetorical strategies that best leverage affect to further the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Although I did not examine social media postings by the march participants, there is little reason to believe the postings will diverge substantially from the march organizers' and participants' views communicated in the news media and shared on the march's website, the mission statement of the march, and two books about the march, one offering research insights from the march participants and another an account by the main organizers of the march. Indeed, in their analysis of 2645 tweets bearing the hashtag of #WhyIMarch on the day of the march, McDuffie and Ames (2021) found that the audience for these tweets appears to have been people similar to the marchers. The authors found that the main rhetorical strategies used in the tweets were "dedications" (marching for someone), "personal narratives," "first person plural pronouns" (used to invoke political allies, among other purposes), and humor.…”
Section: Discussionmentioning
confidence: 99%
“…Although I did not examine social media postings by the march participants, there is little reason to believe the postings will diverge substantially from the march organizers' and participants' views communicated in the news media and shared on the march's website, the mission statement of the march, and two books about the march, one offering research insights from the march participants and another an account by the main organizers of the march. Indeed, in their analysis of 2645 tweets bearing the hashtag of #WhyIMarch on the day of the march, McDuffie and Ames (2021) found that the audience for these tweets appears to have been people similar to the marchers. The authors found that the main rhetorical strategies used in the tweets were "dedications" (marching for someone), "personal narratives," "first person plural pronouns" (used to invoke political allies, among other purposes), and humor.…”
Section: Discussionmentioning
confidence: 99%
“…The first three are high-reach platforms for users in Latin America (Carrasquilla, 2019;Statista, 2021;Vicinitas, 2018), while the latter is on the rise (Ceurvels and Williamson, 2020). Twitter and YouTube have been studied concerning digital activism and feminism (McDuffie and Ames, 2021;Núñez-Puente et al, 2015), while Instagram is only just beginning to be studied in this regard (Özşenler, 2021;Tarullo and García, 2020). There is no previous literature on Latin American feminism and TikTok due to its novelty and recent popularity (Abidin, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…El tuit con más interacciones (Figura 2) es una publicación motivacional que llama a la participación social (McDuffie & Ames, 2021). De esta publicación se pueden inferir tres usos que le ha dado la Campaña a la etiqueta #28S: divulgación de la convocatoria, organización de la acción y presión a los tomadores de decisión.…”
Section: Interacciónunclassified